The role of serum trimethylamine n-oxide and lipopolysaccharide levels in the pathogenesis of chronic gastritis infected with Helicobacter pylori - Kaplankaya, Ugur; Onalan, Erhan; Kaymaz, Tugce; Yakar, Burkay; Atilla, Ruveyda; Bulu, Aykut; Hayirlidag, Mustafa (Bmc, 2025)
Background Helicobacter pylori (HP) infection can cause chronic, intense inflammation of the gastric mucosa, which can lead to stomach cancer. Trimethylamine N-oxide (TMAO) is a dietary metabolite that increases HP virulence and inflammatory process. In this study, we aimed to find out how serum TMAO, lipopolysaccharide (LPS) and pepsinogen levels are affected in patients with HP-induced chronic gastritis. Methods Forty-five age- and sex-matched patients diagnosed with chronic gastritis caused by H. Pylori and 45 healthy controls were included in this cross-sectional study. The diagnosis of H. Pylori-associated chronic gastritis was confirmed by endoscopy and biopsy. Serum TMAO, LPS, pepsinogen 1 and pepsinogen 2 levels were studied by the ELISA method. Results Serum TMAO level of patients with HP gastritis was 48.61 (2.29-120.66) and that of the control group was 7.89 (1.22-76.40). Serum TMAO levels were statistically significantly higher in patients with HP-related chronic gastritis than in the control group (p < 0.001). Serum LPS levels were statistically significantly higher in patients with HP-related chronic gastritis than in the control group (p = 0.008). Serum pepsinogen 1 levels were statistically significantly higher in patients with HP-related chronic gastritis than in the control group (p = 0.001). Conclusion The present study found elevated serum TMAO, LPS and pepsinogen 1 levels in patients with H. Pylori gastritis. These serum markers can be used as a non-invasive method in the evaluation of chronic gastritis infected with H. pylori.
Keywords: Helicobacter pylori; Tr & imath;methylam & imath;ne n-ox & imath;de; Lipopolysaccharide; Chronic gastritis